The Effect of Miming Games on Vocabulary Mastery of Seventh Grade Students at SMP Al-Anwari - Fatimatul Latifah; Inayah, Arin; Wageyono; Abdul Halim (LUNAR, 2025)
The purpose of this research was to determine whether there is an effect of using Miming Game on Vocabulary Mastery. This research used quantitative research method with pre-test and post-test one-group pre-experimental design. The respondents of this research were 19 seventh grade students. The researcher gave a pre-test to students. The pre-test was administered prior to the implementation of the treatment, whereas the post-test was conducted following the completion of the intervention delivered by the researcher. Data collection in this study was carried out through the administration of these tests. T-test analysis formula was used in this research to determine the average difference of post-test and pre-test in the experimental class. The t-test was analyzed and applied interpreted with a significance degree of 5% with df = 19, and obtained a t-table of 1.734. The result of the t-test analysis is 1.7911. This means that the t-test (1.7911) is higher than the t-table (1.734) at 5% significance. Based on the results of the research, it can be concluded that the use of Miming Game as a learning media is effective for vocabulary mastery.